FACTORS ASSOCIATED WITH ALCOHOL USE IN A REPRESENTATIVE SAMPLE OF ADOLESCENTS IN BRAZIL - Larissa Silva Magalhães; Jennifer Barbosa Castro Caetano; Beatriz Zago Martins; Suzy Romere Machado dos Santos; Maria Aparecida da Silva Vieira (Universidade Federal do Paraná, 2024)
Objective: To analyze the factors associated with alcohol use among Brazilian school adolescents. Method: This analytical cross-sectional study uses secondary data from the 2019 National School Health Survey edition conducted by the Brazilian Institute of Geography and Statistics. The research evaluated 125,123 adolescents through the application of a questionnaire. For the final model, multiple logistic regression was used. Results: Lifetime cigarette use was strongly associated with alcohol use (Odds Ratio=3.25; 95% Confidence Interval 2.28-4.62), followed by friends' alcohol use in the last 30 days (Odds Ratio=2.15; 95% Confidence Interval 1.52-3.05) and having parents who smoke (Odds Ratio=1.29; 95% Confidence Interval 1.13-1.48). Conclusion: Integrated actions and public policies involving young people and adolescents are important to ensure the health and well-being of healthy adults.